O „POZYTYWNOŚCI” I „OFICJALNOŚCI” PRAWA W TEORII LEONA PETRAŻYCKIEGO - Tkacz, Sławomir (Wydział Prawa i Administracji UAM, 2005)
The following article deals with the concept of positive law in the theory of Leon Petrażycki. In the first part of his article the author presents different characteristics of the term positive law encountered in literature. The analysis of the term serves as a starting point for further study aiming at answering the question whether Petrażycki’s concept of positive law relates to other characteristics of the term in literature or whether the author introduces a new understanding of law positiveness. In the second part of the article the author analyses the varieties of law distinguished by Petrażycki. He is paying special attention to Pitrażycki’s division of law into positive and intuitive and describes the categories of positive law. Additionally, he mentions another Petrazycki’s typology: official vs. unofficial types of law; official law is applied by state authorities. The author’s reasoning leads to the general conclusion that Petrażycki’s definition of positive law corresponds neither with the understanding of the term in the theories of natural law as opposed to positive law, nor with the understanding of positive law as proposed by classical positivism. Furthermore, the author points to the fact that it is generally agreed that a number of views in the contemporary law theory were influenced by Petrażyckis works. This opinion is shared even by those who represent the view that law characteristics in Petrażycki’s theory is not an analytical definition but only a linguistic convention; as well as by those who think that he constructed a kind of idealistic theory which refers to the law described as a group of psychological phenomena. That is why the author concludes that both the interpretation of Petrażycki’s views and the influence of his concepts on the Polish contemporary theory of law require further scientific research.
THE POSITIVE AND OFFICIAL QUALITY OF LAW IN LEON PETRAŻYCKTS THEORY